2018
DOI: 10.1038/s41467-018-03803-x
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative STAT/NF-κB signaling regulates lymphoma metabolic reprogramming and aberrant GOT2 expression

Abstract: Knowledge of stromal factors that have a role in the transcriptional regulation of metabolic pathways aside from c-Myc is fundamental to improvements in lymphoma therapy. Using a MYC-inducible human B-cell line, we observed the cooperative activation of STAT3 and NF-κB by IL10 and CpG stimulation. We show that IL10 + CpG-mediated cell proliferation of MYClow cells depends on glutaminolysis. By 13C- and 15N-tracing of glutamine metabolism and metabolite rescue experiments, we demonstrate that GOT2 provides aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 69 publications
1
64
0
Order By: Relevance
“…Metabolite extraction was performed with 80% methanol. Amino acids isotopologues were analyzed by high performance liquid chromatography (HPLC)-electrospray ionization (ESI)-tandem MS (MS/MS) after propyl chloroformate derivatization and intermediates of glycolysis and TCA cycle by GC-MS after derivatization using methoximation and silylation (Feist et al, 2018;Loftus et al, 2018). All raw data were corrected for natural stable isotope abundance and tracer impurity using IsoCorrectoR .…”
Section: -Glucose Tracer Analysismentioning
confidence: 99%
“…Metabolite extraction was performed with 80% methanol. Amino acids isotopologues were analyzed by high performance liquid chromatography (HPLC)-electrospray ionization (ESI)-tandem MS (MS/MS) after propyl chloroformate derivatization and intermediates of glycolysis and TCA cycle by GC-MS after derivatization using methoximation and silylation (Feist et al, 2018;Loftus et al, 2018). All raw data were corrected for natural stable isotope abundance and tracer impurity using IsoCorrectoR .…”
Section: -Glucose Tracer Analysismentioning
confidence: 99%
“…Analyses of amino acids and organic acids from stable isotope tracer experiments were performed using HPLC-MS/MS and GC-MS after derivatization, respectively, as described recently (55). All expected isotopologs were analyzed.…”
Section: Tracer Experimentsmentioning
confidence: 99%
“…The potential feed-forward loop of BRCA1/ZBRK1/GOT2 may be a crucial metabolic driver signaling BC progression. Recently, GOT2 was shown to activate transcriptionally STAT3/NF-jB in IL-10 responsiveness (Feist et al, 2018). One may propose that GOT2 is fine-tuned with different cell metabolic status and different stimuli in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, aspartate metabolism reprogramming exists in many cancers, including hepatocellular carcinoma (Darpolor et al, 2014), pancreatic cancer (Yang et al, 2015(Yang et al, , 2018, leukemia (Sullivan et al, 2015), lung cancer, cervical cancer, osteosarcoma and glioblastoma (Sullivan et al, 2015). GOT2 converts glutamate and oxaloacetate to generate aspartate and a-KG, which is the critical enzyme for maintaining the aspartate pool (Feist et al, 2018). Previous studies have revealed that a crucial role of cellular respiration is to maintain redox homeostasis to support aspartate and therefore biomass production and rapid proliferation (Birsoy et al, 2015;Sullivan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation